The Structure of Import Tariffs in Russia : 2001-2003 - Tarr, David; Shepotylo, Oleksandr; Koudoyarov, Timour (World Bank, Washington, DC, 2017)
What is the structure of the Most-Favored Nation (MFN) tariff of Russia? How has it been changing over time? What are the sectors in which tariffs are high or low? How diverse is the tariff structure of Russia? Surprisingly, these questions have not been answered to date due to a lack of data that would allow calculation of the ad valorem equivalents of the specific Russian tariffs. The authors have obtained a new data set that they describe in this book. As a result of these new data, the authors are able to calculate the ad valorem equivalents of the specific tariffs. This allows them to provide the first detailed and accurate assessment of the tariff structure of Russia. The authors are able to assess, for the years 2001-2003, the actual number of tariff lines in which specific tariffs apply, what are the tariff lines with the highest tariffs, and investigate many other properties of the Russian tariff structure for the first time. This book is arranged as follows: In section two the authors discuss the key results. The authors calculate average tariffs and standard deviations based on an unweighted basis and also an import trade weighted basis. In section three the authors discuss the data set. The authors discuss methodology in section IV. The key results are presented in tables 1-8. The authors have a one-page note on technical details in the calculations following the tables. In Appendix A the authors present tables with more detailed results, namely of 2-digit industry calculations and the tariff lines with tariff rates above 50 percent. In appendix B, the authors provide a second set of parallel tables called Estimated collected tariff rates. These tables reflect the fact that imports from CIS countries enter tariff free with some notable exceptions, so the collected tariff rate is lower than the MFN rate. As the authors discuss the results, they evaluate the trends in the tariff structure based on the view, elaborated by Tarr (2002), that low and uniform tariffs are preferable to high and diverse tariffs. This paper is methodological and descriptive, so the reader interested in a discussion of tariff policy should consult Tarr (2002).